2021
DOI: 10.1086/713446
|View full text |Cite
|
Sign up to set email alerts
|

Ex Situ Conservation of Large and Small Plant Populations Illustrates Limitations of Common Conservation Metrics

Abstract: Premise of research. Ex situ plant conservation can be improved through genetic analysis. One area of interest is the relative value of conserving smaller or larger populations and how sampling strategies for these might differ. Current practice emphasizes collecting large sample sizes from some populations and limiting sampling from others and aims for the capture of allele diversity exceeding predetermined thresholds at the species level. Evaluating how well botanic garden collections can capture the genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…Both the nucleotide diversity and expected heterozygosity in the two ex situ populations (GXF and GXG1) were higher than those in the wild populations (Table 1 ), which may be attributed to the direct transplantation of wild seedlings as this type of material allows the preservation of genetic diversity from different maternal lines (Griffith et al, 2021 ). In terms of genetic structure (Figure 2c ), the GXG1 population was found to have the most complex origin of the ex situ populations which may have come from multiple different maternal lineages.…”
Section: Discussionmentioning
confidence: 97%
“…Both the nucleotide diversity and expected heterozygosity in the two ex situ populations (GXF and GXG1) were higher than those in the wild populations (Table 1 ), which may be attributed to the direct transplantation of wild seedlings as this type of material allows the preservation of genetic diversity from different maternal lines (Griffith et al, 2021 ). In terms of genetic structure (Figure 2c ), the GXG1 population was found to have the most complex origin of the ex situ populations which may have come from multiple different maternal lineages.…”
Section: Discussionmentioning
confidence: 97%
“…Although for SCK and SH all populations sampled had at least the minimum of 20 individuals suggested to assess allele diversity in forest trees (Rodríguez‐Peña et al, 2018) this was not the case for NEK where only 7 of 18 populations did so. However, small populations can still provide useful insights into genetic structure and diversity at the population and regional levels (Griffith et al, 2021; Pruett & Winker, 2008). Thus, we used all populations for all analyses (unless otherwise specified) except for the 23‐SAS population which consisted of only one individual.…”
Section: Methodsmentioning
confidence: 99%
“…It was found that pooled collections from more than one garden captured more genetic diversity than a single-garden collection, and captured it more efficiently (Griffith et al, 2020). Study of its sister species (P. sargentii) showed that tailored collection protocols for small and large populations should be considered, and that emphasis on maximizing maternal lines in a collection captures genetic diversity most efficiently (Griffith et al, 2021). Furthermore, comparing P. sargentii and P. ekmanii among non-palm species showed that taxonomic closeness does not predict genetic capture in ex situ collections (Hoban et al, 2020).…”
Section: Collections Genetics Of Palmsmentioning
confidence: 99%